Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Berpikir Kritis dan Kepercayaan Diri Peserta Didik - Ronisius Otu; C. Asri Budiningsih (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of the PBL model on students' critical thinking skills and self-confidence at State Senior High School 1 Amanuban Tengah, East Nusa Tenggara Province. This research was experimental research and the quasi-experimental design used in this research is a pretest-posttest control group design. The research results showed that the pretest average of critical thinking skills in the experimental class was 37.21, while in the control class, it was 37.14. The average prescale self-confidence score of students in the experimental class was 48.66, while in the control class, it was 48.60. Furthermore, the posttest average of critical thinking skills in the experimental class was 65.71, and in the control class was 45.71. The data analysis used the independent samples test method on students' critical thinking skills variable obtained a significance value (sig. 2-tailed) = 0.000 <0.05 and also on the students' self-confidence variable obtained a significance value (sig. 2-tailed) = 0.000 <0.05, which means H0 rejected and Ha accepted. Based on the results of the research, it can be concluded that the PBL model has a positive effect on the student's critical thinking skills and self-confidence in senior high school.